Pancreatoblastoma with Portal Venous Invasion: A Case Series - Pooja Abbey (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
We describe the sonography and computed tomography (CT) findings in three children with pancreatoblastoma and highlight the tendency of these tumors to invade the splenoportal axis. All three of our cases showed tumor thrombus within the portal vein which is a helpful diagnostic feature on imaging studies.